Prediction model of spontaneous combustion temperature intervals of coal samples from multiple mining regions - Qiaojun Chen; Jianhong Kang; Chengyang Peng; Ran Zhang; Jiakuo Tian; Chuanheng Yang; Anxuan Chen (Fuel, 2026)

Botulinum toxin injection combined with rehabilitation training for peroneal spastic flatfoot: A pilot case series - Ran Zhang; Yaping Chen; Xiuying Huang; Yuxin Tian; Lu Wang (Toxicon, 2026)

Inhibition of Sonic Hedgehog signaling pathway by GANT61 alleviates adenomyosis by suppressing epithelial-to-mesenchymal transition, cell migration and proliferation - Zaifan Lin; Simiao Yan; Qingzhen Ran; Qianxin Yang; Haixin Lin; Jingtong Sun; Yi Chen; Xiuchi Zhong; Yingzhou Tian; Wanqun Chen (Tissue and Cell, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Phytochemical composition of Alpinia japonica rhizome essential oil and its antibacterial, anticancer, and enzyme inhibitory activities - Xiaoqing Zhao; Qiong Hu; Yuanquan Ran; Guo Chen; Bing Yang; Tian Zhang; Dongxin Tang; Minyi Tian (Biochemical Systematics and Ecology, 2026)

Construction of the CRISPR/Cas12a-digital integrated immunoassay technology for CD44 detection - Songbai Tian; Xin Tang; Saijun Zhang; Yuexin Yao; Ran Bi; Haixia Li; Xiaoming Sun; Zhuo Chen (Analytica Chimica Acta, 2026)

Direct synthesis of non-migratory, intrinsically antioxidant ultra-high molecular weight polyethylene by nickel catalysis - Fei-Ran Yang; Wen-Bing Wang; Tian-Ming Yang; Hao-Xiang Sun; Quan Wang; Meng-He Xu; Jia-Wei Chen; Chen Zou (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Cation-size-directed interfacial and electronic engineering of Ti3C2Tx MXenes via ionic liquid intercalation for high-rate proton storage - Jeremiah Hao Ran Huang; Wei-Siang Lo; Yu-Ting Tai; Yu-Chun Shih; Hong-Kang Tian; I-Wen Peter Chen (Chemical Engineering Journal, 2026)

A self-oxygenating, ROS-responsive nanoplatform potentiates sonodynamic-immunotherapy via STING activation in pancreatic cancer - Qiyi Feng; Xiao Wen; Chunxiu Xiao; Zhifan Wang; Qingqing Ran; Ling Wang; Sisi Yi; Xiuli Zheng; Zhaoyan Chen; Fangyuan Tian; Junjie Xiong; Haibo Wang; et al. (Chemical Engineering Journal, 2026)

The impact of atmospheric aging processes on the ice nucleation activity of Asian dust: A perspective from online continuous flow diffusion chamber observations - Jiayun Li; Xinyuan Chang; Dantong Chen; Kai Bi; Yunbo Chen; Xincheng Ma; Ruijie Li; Ping Tian; Mengyu Huang; Xiaoyu Ren; Shuai Wang; Zhaoze Deng; et al. (Atmospheric Pollution Research, 2026)

The CMA Chemistry–Weather Coupled Model and Its Operational Forecast of Fog–Haze and Sand/Dust Storms - Hong Wang; Xiaoye Zhang; Wenjie Zhang; Yue Peng; Ping Wang; Hongli Liu; Zhaorong Zhuang; Liping Huang; Weihong Tian; Yang Zhao; Ke Gui; Chen Han; et al. (Journal of Meteorological Research, 2026)

GNAS drives gastric cancer progression via pyrimidine metabolic reprogramming and immune-microenvironment remodeling - Xinyi Wang; Heng Tian; Jiaju Wang; Yafen Wang; Ran Wei; Yuhan Liu; Yun Hong; Fan Wang; Bangjie Chen (Apoptosis, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Corrigendum to “Ultra-sensitive gas sensor enabled by architectural and electronic synergy in bio-templated ZnO/hollow carbon microtubules” [J. Environ. Chem. Eng. 14 (2026) 121787] - Chuanxi Li; Shengxi Chen; Bing Gao; Yueheng Niu; Bo Ran; Yibo Han; Zhaofeng Wu; Ning Tian; Qun Jing (Journal of Environmental Chemical Engineering, 2026)

Regulatory patterns of antibody-dependent cellular phagocytosis–related genes in triple-negative breast cancer: An integrated multi-omics and single-cell analysis - Guihua Hong; Zhanyue Cui; Xiaowen Xu; Shiwei Lin; Changqing Yang; Ran Ding; Ludan Liang; Ying Chen; Ziyue Tian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Strontium and cesium accumulation in soil-rice system: Influencing factors and predictive modeling - Hong-Ling Chen; Bao-Min Yao; Zi-Yang Pan; Dong-Li Sun; Guang Yang; Tian-Ran Sun; Guo-Xin Sun (Soil Ecology Letters, 2026)

Toxoplasma GRA72 is Involved in Membrane-Associated Functions and Metabolic Homeostasis Revealed by Transcriptomic Analysis - Xin-Sheng Lu; Xing Tian; Jing Li; Chen-Ran Tian; Xing-Quan Zhu; Xiao-Nan Zheng (Acta Parasitologica, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Ultra-sensitive gas sensor enabled by architectural and electronic synergy in bio-templated ZnO/hollow carbon microtubules - Chuanxi Li; Shengxi Chen; Bing Gao; Yueheng Niu; Bo Ran; Yibo Han; Zhaofeng Wu; Ning Tian; Qun Jing (Journal of Environmental Chemical Engineering, 2026)

Nanogel-encapsulated Rosa roxburghii Tratt fruit polyphenols ameliorated ulcerative colitis by regulating gut microbiota and PI3K/Akt and NF-κB pathways - Mingxiu Long; Hui Wang; Fang Zhang; Yaoqi Ran; Yongfu Li; Jingwen Luo; Zhaojun Chen; Zhuxi Tian; Shuming Tan; Xiong Liu (Food Research International, 2026)

Associations of air pollution and genetic risk and their interaction with risk of Alzheimer’s disease: identification of risk loci and potential biological pathways - Shanshan Ran; Jingyi Zhang; Miao Cai; Lan Chen; Zhengmin Qian; Fei Tian; Gan Wu; Ri’enna Boyd; Stephen Edward McMillin; Huai-cai Zeng; Yin Yang; Hualiang Lin (GeroScience, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Biochar and iron minerals facilitate the reduction of pollution and sequestration of carbon in chloramphenicol-contaminated soil under dry conditions - Pengfei Cheng; Junliang Chen; Ran Xu; Qin Tian; Xiaobo Luo; Zhicong Dai; Zhiliang Li; Yao Lu; Lianghui Li; Kuan Cheng; Chao Guo; Guanlin Li; et al. (Applied Soil Ecology, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Millennial-scale episodic coral growth on the northern margin of the South China Sea - Yuyang Lin; Tian-ran Chen; Nicole D. Leonard; Jian-xin Zhao (Global and Planetary Change, 2025)

Electrostatic-modulated assembly of charged COF nanosheets into high-performance nanofiltration-based desalination membranes - Shan Luo; Ran Chen; Ruiyuan Zeng; Dai Shi; Youqing Tian; Jiamei Sun; Zifan Song; Yuanhui Xiao; Jiashu Yuan; Jianghuan Shi; Haixiong Liu; Hanyang Liu; et al. (Chemical Engineering Journal, 2025)

Phytochemical characterization, antioxidant, enzyme inhibitory and anti-inflammatory activities of Hedychium coccineum Buch.-Ham. ex Sm. rhizome - Yuanquan Ran; Dan Xie; Dan Long; Lu Jin; Guo Chen; Bing Yang; Dongxin Tang; Minyi Tian (Biochemical Systematics and Ecology, 2025)

Terrestrial–aquatic microbial community coalescence slows litter decomposition in forest streams - Han Jiang; Yinghui Yang; Jiawen Liang; Run Liu; Yueting Pan; Tingting Cao; Siyuan Chen; Zunian Ran; Chang Zhao; Yanli Tian; Xingjun Tian (Plant and Soil, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cu+ -loaded complex adsorbent in acid modified bentonite for improving carbon monoxide (CO) capture - Jianwei Cheng; Yifan Li; Rui Zhang; Dezhi Ran; Zuyun Chen; Wenhao Hou; Qiang Fu; Zhiguang Tian (Process Safety and Environmental Protection, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Soot particles generated by n-heptane and n-heptane/OME3 in an inverse diffusion flame: A comparative analysis of physical properties and oxidative reactivity - Ye Liu; Ran Zhang; Chenxi Wang; Haibo Chen; Gang Lyu; Jun Wang; Huayu Tian; He Yang; Yajun Wang; Chenyang Fan; Bin Xu; Xiaowei Wang; et al. (Fuel, 2025)

In situ transglutaminase cross-linking mediated protein-stabilized high internal phase emulsion gels to emulate dorsal adipose tissue: The role of continuous phase networks - Liang Guo; Yu-hang Xue; Yi-ran Zhang; Wen-yan Chen; Yao-siyi Yuan; Shen-shen Tian; Yue-Cheng Meng; Jie Chen (Food Chemistry, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Constructing and Evaluating Predictors for Data-Driven PM2.5 Forecasting Models - Ran-Ran He; Yu-Qiao Chen; Lei Tian; Lei Shan; Xiao-Shuang Sang (International Journal of Environmental Research, 2025)

Sustained release of gaseous chlorine dioxide from alpha-cyclodextrin: An innovative method for strawberry preservation - Linyan Chen; Haohan Jing; Yuhe Dong; Yuantong Cao; Tong Wu; Wanying Zhu; Fanwei Dai; Minhui Chen; Yao Liu; Nan He; Ran Huang; Tian Zhong (Food Chemistry, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Mechanism allowing biochar to aid in arbuscular mycorrhizal colonization in Panax quinquefolius L. roots and improve secondary metabolite production - Xiaoli Chen; Zhifang Ran; Yue Wang; Tian Chen; Lanping Guo; Lei Fang; Jie Zhou (Mycorrhiza, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Microplastics and copper impacts on feeding, oxidative stress, antioxidant enzyme activity, and dimethylated sulfur compounds production in Manila clam Ruditapes philippinarum - Yu Jiang; Juan Yu; Ji-Yuan Tian; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song; Rong Chen (Marine Pollution Bulletin, 2024)

Cu/Fe3O4 magnetic aerogel for the capture and immobilization of iodine anion from water - Xin-Yu Zhou; Kai-Wei Chen; Ao-Tian Gu; Hui-Ran Jin; Wei-Jie Sun; Shu-Chao Song; Shan Yun; Ping Mao; Yi Yang; Jing Chen (Journal of Cleaner Production, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Exploring secondary aerosol formation associated with elemental carbon in the lower free troposphere - Li Li; Qiyuan Wang; Jie Tian; Yaqing Zhou; Nan Ma; Huikun Liu; Yang Zhang; Shuoyuan Chen; Jin Wang; Yukun Chen; Weikang Ran; Jianjun Li; et al. (Science of The Total Environment, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Variations in the concentration, inventory, source, and ecological risk of polycyclic aromatic hydrocarbons in sediments of the Lake Chaohu - Hao-Ran Tian; Xi-Tao Zhang; Li-Li Zhao; Shu-Chuan Peng; Ji-Zhong Wang; Yi-Han Chen (Marine Pollution Bulletin, 2024)

Soil Cd increased the leaf litter Cd remains of Solanum nigrum and Solanum lycopersicum - Qi Chen; Yuxuan Feng; Zunian Ran; Zeyan Zhou; Qianwei Li; Yunchao Luo; Sulin Cai; Siyuan Chen; Junbo Yang; Xingjun Tian (Environmental Pollution, 2024)

Co-pyrolysis mechanism of polyester enameled wire and PVC: A joint experimental and theoretical investigation - Ran Tao; Bin Li; Yufeng Wu; Zhongxun Tian; Wei Zhang; Haoran Yuan; Jing Gu; Yong Chen (Journal of Cleaner Production, 2024)

π-π Stacking constructing efficient charge channels for perovskite photovoltaics - Chun-Hao Chen; Fan Hu; Kai-Li Wang; Jing Chen; Tian-Yu Teng; Yi-Ran Shi; Yu Xia; Zhen-Huang Su; Xing-Yu Gao; Ilhan Yavuz; Zhao-Kui Wang; Liang-Sheng Liao (Science Bulletin, 2024)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Exercise preconditioning promotes myocardial GLUT4 translocation and induces autophagy to alleviate exhaustive exercise-induced myocardial injury in rats - Yuan-Pan Guo; Shan-Shan Pan; Tian-Ran Chen; Yue Huang; Dong-Feng Wan; Yi-Shan Tong (Journal of Molecular Histology, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Heterogeneous characteristics and absorption enhancement of refractory black carbon in an urban city of China - Shuoyuan Chen; Qiyuan Wang; Yong Zhang; Jie Tian; Jin Wang; Steven Sai Hang Ho; Li Li; Weikang Ran; Yongming Han; Giulia Pavese; Junji Cao (Science of The Total Environment, 2023)

Effects of cryopreservation on the biomechanical properties of dentin in cryopreserved teeth: An in-vitro study - Juan Xu; Yue Chen; Min Zhou; Shouyin Yi; Juan Ran; Juanxiu Liu; Junzhou Chi; Zhu Chen; Kun Tian (Cryobiology, 2023)

Remote estimation of leaf water concentration in winter wheat under different nitrogen treatments and plant growth stages - Li He; Meng-Ran Liu; Shao-Hua Zhang; Han-Wen Guan; Chen-Yang Wang; Wei Feng; Tian-Cai Guo (Precision Agriculture, 2023)

Composite lining-ground interaction behavior in a cold-region circular tunnel under isotropic frost heave action - Hongwei Li; Yuanming Lai; Huyuan Zhang; Yanyan Chen; Wangtao Jiang; Yan Tian; Jiachuan Ran (Cold Regions Science and Technology, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Effects of carbonate minerals and exogenous acids on carbon flux from the chemical weathering of granite and basalt - Chaojun Li; Pete Smith; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Qin Li; Jinfeng Wang; Luhua Wu; Fei Chen; Yuanhong Deng; Zeyin Hu; Yujie Yang; et al. (Global and Planetary Change, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

MdMYB88/124 modulates apple tree microRNA biogenesis through post-transcription processing and/or transcription pathway - Chun-dong Niu; Huan-ran Shi; Zi-tong Zhang; Tian-le Fan; Huan Dang; Peng-xiang Chen; Yin-peng Xie; Cha-na Bao; Feng-wang Ma; Qing-mei Guan; Xue-wei Li (Acta Physiologiae Plantarum, 2022)

Genomewide analysis of sperm whale E2 ubiquitin conjugating enzyme genes - Ran Tian; Chen Yang; Yuepan Geng; Inge Seim; Guang Yang (Journal of Genetics, 2021)

Comparison of myocardial ischemic/hypoxic staining techniques for evaluating the alleviation of exhaustive exercise-induced myocardial injury by exercise preconditioning - Yue Huang; Shan- Shan Pan; Yuan-Pan Guo; Jia-Yin Wang; Dong-Feng Wan; Tian-Ran Chen; Jian-Qi Yuan (Journal of Molecular Histology, 2021)

Performances of six eupelmid egg parasitoids from China on Japanese giant silkworm Caligula japonica with different host age regimes - Yong-Ming Chen; Xing-Ran Qu; Tian-Hao Li; Asim Iqbal; Xingeng Wang; Zhi-Yong Ren; Nicolas Desneux; Lian-Sheng Zang (Journal of Pest Science, 2021)

Aberration of Serum and Tissue N-Glycans in Mouse β1,4-GalT1 Y286L Mutant Variants - Ran Cao; Tian-Chan Zhang; Ya-Ran Chen; Cui Cao; Huan Chen; Yi-Fan Huang; Morihisa Fujita; Li Liu; Josef Voglmeir (Glycoconjugate Journal, 2020)

Spatial homogenization of soil-surface pollen assemblages improves the reliability of pollen-climate calibration-set - Fang Tian; Xianyong Cao; Ran Zhang; Qinghai Xu; Wei Ding; Xingqi Liu; Baolin Pan; Jianhui Chen (Science China Earth Sciences, 2020)

Cerebellar Atrophy in Multiple System Atrophy (Cerebellar Type) and Its Implication for Network Connectivity - Hao Zhang; Shaozhen Ji; Shan Ren; Ming Liu; Weizheng Ran; Xinning Zhang; Wenyang Tian; Zhigang Chen; Zhiqun Wang (The Cerebellum, 2020)

Remediation of Trichloroethylene-Contaminated Groundwater by Sulfide-Modified Nanoscale Zero-Valent Iron Supported on Biochar: Investigation of Critical Factors - Jie Chen; Haoran Dong; Ran Tian; Rui Li; Qianqian Xie (Water, Air, & Soil Pollution, 2020)

Sustainable strategy for municipal solid waste disposal in Hong Kong: current practices and future perspectives - Ran Jing; Tongzhou Liu; Xin Tian; Hamidreza Rezaei; Chen Yuan; Jin Qian; Zhen Zhang (Environmental Science and Pollution Research, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Bioactive compounds from Cudrania tricuspidata: A natural anticancer source - Xusheng Li; Zilan Yao; Xinwei Jiang; Jianxia Sun; Guojing Ran; Xuan Yang; Yaqi Zhao; Ying Yan; Zisheng Chen; Lingmin Tian; Weibin Bai (Critical Reviews in Food Science and Nutrition, 2020)

Detection of a thin layer by seismic reflection with different geophones at a site in Liangzhu, Southeastern China - Abdullah Lizan; Gang Tian; Yimin Wang; Ran Chen; Shahid Shaihk; Haiyan Liu (Arabian Journal of Geosciences, 2019)

RNA-Seq-based transcriptomic profiling of primary interstitial cells of Cajal in response to bovine viral diarrhea virus infection - Shengnan Li; Xinyan Hu; Ruixin Tian; Yanting Guo; Junzhen Chen; Zhen Li; Xinyan Zhao; Ling Kuang; Duoliang Ran; Hongqiong Zhao; Xiaohong Zhang; Jinquan Wang; et al. (Veterinary Research Communications, 2019)

Bituminous coal combustion and Xuan Wei Lung cancer: a review of the epidemiology, intervention, carcinogens, and carcinogenesis - Jinhui Li; Jinjun Ran; Lung-chi Chen; Max Costa; Yunchao Huang; Xiao Chen; Linwei Tian (Archives of Toxicology, 2019)

Divergent Selection of Pattern Recognition Receptors in Mammals with Different Ecological Characteristics - Ran Tian; Meixiu Chen; Simin Chai; Xinghua Rong; Bingyao Chen; Wenhua Ren; Shixia Xu; Guang Yang (Journal of Molecular Evolution, 2018)

Ultrastructure of ellipsoidal magnetotactic multicellular prokaryotes depicts their complex assemblage and cellular polarity in the context of magnetotaxis - Pedro Leão; Yi‐Ran Chen; Fernanda Abreu; Mingling Wang; Wei‐Jia Zhang; Ke Zhou; Tian Xiao; Long‐Fei Wu; Ulysses Lins (Environmental Microbiology, 2017)
Summary Magnetotactic multicellular prokaryotes (MMPs) consist of unique microorganisms formed by genetically identical Gram‐negative bacterial that live as a single individual capable of producing magnetic nano‐particles called magnetosomes. Two distinct morphotypes of MMPs are known: spherical MMPs (sMMPs) and ellipsoidal MMPs (eMMPs). sMMPs have been extensively characterized, but less information exists for eMMPs. Here, we report the ultrastructure and organization as well as gene clusters responsible for magnetosome and flagella biosynthesis in the magnetite magnetosome producer eMMP Candidatus Magnetananas rongchenensis. Transmission electron microscopy and focused ion beam scanning electron microscopy (FIB‐SEM) 3D reconstruction reveal that cells with a conspicuous core‐periphery polarity were organized around a central space. Magnetosomes were organized in multiple chains aligned along the periphery of each cell. In the partially sequenced genome, magnetite‐related mamAB gene and mad gene clusters were identified. Two cell morphologies were detected: irregular elliptical conical ‘frustum‐like’ (IECF) cells and H‐shaped cells. IECF cells merge to form H‐shaped cells indicating a more complex structure and possibly a distinct evolutionary position of eMMPs when compared with sMMPs considering multicellularity.

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

The biochemical and immunological characterization of two serpins from Clonorchis sinensis - Huali Lei; Yanli Tian; Wenjun Chen; Xiaoyun Wang; Xuerong Li; Qiang Mao; Jiufeng Sun; Ran Li; Yanquan Xu; Chi Liang; Yan Huang; Xinbing Yu (Molecular Biology Reports, 2013)

Effects of the Metals Lead and Zinc on the Growth, Development, and Reproduction of Pardosa Astrigera (Araneae: Lycosidae) - Xiao-qiong Chen; Zheng-tian Zhang; Ran Liu; Xiu-Ling Zhang; Jian Chen; Yu Peng (Bulletin of Environmental Contamination and Toxicology, 2011)